Sustainable development and guidance for entrepreneurship in unfavoured regions: the case of the Alentejo region - Fragoso, Rui (2016)
The unfavoured Portuguese regions have a level of life and economic growth rates lower than favoured regions, and the mean of European Union and hence have less entrepreneurial activities. The adoption of strategies of sustainable development driven by entrepreneurship phenomena could be a viable solution. Thus, the likely relationships between entrepreneurship and regional features were described, and sources of entrepreneurship opportunities for strategies based on the own regional resources and competitive advantages were identified. The paper concludes that for the Alentejo region, some habitat variables should be reinforced for promoting entrepreneurship and sustainable development, and the main opportunities are related to the economic activities that belong to the regional productive profile of specialisation